Oncogenic transcription factors as master regulators of chromatin topology: A new role for ERG in prostate cancer - Elemento, Olivier (Landes Bioscience, 2012)
The three-dimensional (3D) conformation of the genome is known to be structured and to affect gene transcription, but how chromatin conformation changes in diseases such as cancer is poorly understood. Similarly, oncogenic transcription factors bind to thousands of sites in the genome without a clear transcriptional role on nearby genes. Could these factors play a non-transcriptional role in promoting tumor progression by restructuring the shape of the genome? To address this question, we recently performed unbiased high-resolution mapping of intra- and inter-chromosome interactions upon overexpression of ERG, an oncogenic transcription factor frequently overexpressed in prostate cancer as a result of a gene fusion. By integrating data from genome-wide chromosome conformation capture (Hi-C), ERG binding and gene expression, we have demonstrated that oncogenic transcription factor overexpression is associated with global, reproducible and functionally coherent changes in chromatin organization. Perhaps more importantly, we have identified novel genomic alterations associated with ERG overexpression. These results suggest a yet unappreciated role for transcription factors in promoting genomic alterations through their effect on chromatin architecture.